Epidemiological associations between iron and cardiovascular disease and diabetes - Basuli, Debargha; Stevens, Richard G.; Torti, Frank M.; Torti, Suzy V. (Frontiers in Pharmacology, 2014)
Disruptions in iron homeostasis are linked to a broad spectrum of chronic conditions including cardiovascular, malignant, metabolic and neurodegenerative disease. Evidence supporting this contention derives from a variety of analytical approaches, ranging from molecular to population-based studies. This review focuses on key epidemiological studies that assess the relationship between body iron status and chronic disease, with particular emphasis on atherosclerosis and diabetes/ metabolic syndrome. Multiple surrogates have been used to measure iron status, including serum ferritin, transferrin saturation, serum iron, and dietary iron intake. The lack of a uniform and standardized means of assessing body iron status has limited the precision of epidemiological associations. Intervention studies using depletion of iron to alter risk have been conducted. Genetic and molecular techniques have helped to explicate the biochemistry of iron metabolism at the molecular level. Plausible explanations for how iron contributes to the pathogenesis of these chronic diseases are beginning to be elucidated. Most evidence supports the hypothesis that excess iron contributes to chronic disease by fostering excess production of free radicals. Overall, epidemiological studies, reinforced by basic science experiments, provide a strong line of evidence supporting the association between iron and elevated risk of cardiovascular disease and diabetes. In this narrative review we attempt to condense the information from existing literature on this topic.